Doing discourse research an introduction for social scientists - Keller, Reiner (SAGE, 2013)
This book provides an introduction to the basic principles of discourse research and provides practical research strategies for doing discourse analyses in the social sciences. The book includes guidance on developing a research question, selecting data and analysing it, and presenting your results. The author has extensive practical experience in the field of discourse research and shows throughout how the methods suggested are compatible with numerous research questions and problems in sociology, cultural, political and social studies and related disciplines.